Novel Microstrip Antenna Design - A., Hameed; Oudah, Ali A.; Izzeldin, I. Mohd (Science and Engineering Research Support Society, 2014)
A simple, small, compact, low cost, and practical antenna for 2.4 GHz applications is proposed in this paper. A detailed investigation on miniaturized microstrip planar antenna design using a combination of proposed shorted patch and meandering method are presented. All design and simulations are done using Computer Simulation Studio (CST) software. For accuracy reasons, verification has been done, all the designs were fabricated, and measurements on return loss and impedance bandwidth were implemented by using RF Analyzer